Leadership management role as determinant of students' academic achievement in high schools in Osun State, Nigeria (2017)
This study investigated high school principals' ability to perform managerial role as determinant of students' academic achievement in Osun State. Three research questions were developed to guide the study. The study adopted ex-post facto design of survey research type in which 124 principals of high schools in Osun State were purposively selected. Data was collected using a self-designed questionnaire. Pearson Product Moment Correlation and Multiple Regression were utilised for data analysis at 0.05level of analysis. The study's finding revealed that the managerial roles of principals had no significant composite influence on students' academic performance [F (5,241) = 0.985], (R) = 0.142 and, R square of 0.020. That is, academic achievement of students in schools had no correlation with principals' roles. This means that 1.0% (Adj. R2=0.010) of the variance in the academic achievement in schools accounted for the independent variables, when taken together. Also, managerial role has no significant relative influences on students' academic performance. Planning (β = 0.003, t= .025, p> 0.05) has no potent contribution to the prediction, organising role has no significant influence (β = 0.086, t= .794, p> 0.05) and directing had no significant influence (β = 0.029, t= 0.293, p> 0.05). The study, therefore, recommended that school principals in the state should endeavour to discharge their managerial roles or functions in such a way that will create positive impact on students' academic achievement.